Addressing gender inequalities in health: a comprehensive framework for policy and practice - Zeinab Khaledian; Maryam Tajvar; Amirhossein Takian; Mehdi Yaseri; Mohammad Hajizadeh; Alireza Olyaeemanesh (Discover Social Science and Health)
Abstract Background Despite evidence on the role of gender as a social determinant of health, there is a lack of frameworks that focus on the factors contributing to gender inequalities in health (GIeH) and their specific characteristics. We aim to present the GIeH framework, specifically designed to illustrate the processes, determinants, and consequences of GIeH that support improved measurement of gender equality in health and inform policymaking. Methods A ‘best-fit’ framework synthesis was utilized. We identified the existing frameworks to generate an a priori framework, followed by systematically identifying relevant studies and coding their results against it. We searched bibliographic databases including Web of Science, MEDLINE, PubMed, ScienceDirect, Scopus, and grey literature and relevant websites, using predefined inclusion and exclusion criteria. No restrictions were imposed on document type, setting, date, or language and we used the JBI critical appraisal checklist to assess the quality of included studies. Thematic analysis and team discussions were applied to finalize the sub-themes in our proposed conceptual framework. Results Based on the synthesis of identified evidence, we categorized eight themes and 48 sub-themes into determinants and consequences of GIeH. These determinants were classified into four layers: context, health system, community-household, and individual factors. We provided a schematic to illustrate the interaction process between these layers, contributing to gender inequalities in health outcomes such as health status, life expectancy, health- related quality of life, mortality, and morbidity. Conclusion This framework provides a broad perspective on gender inequalities in health. It is a practical tool for health policymakers and professionals, providing a systematic approach to measure, monitor, and address these inequalities. By highlighting the interactions of various factors from Micro to Macro level and their effects on health outcomes, the framework facilitates strategic policy interventions and empirical solutions to promoting health equity. Systematic review registration: PROSPERO; CRD42022366765.